Aunt Chip and the great Triple Creek dam affair - Polacco, Patricia (New York : Scholastic Inc., 1996)
Aunt Chip saves the town of Triple Creek, where everyone has forgotten how to read because of the invasion of television.
Reprint: Originally published: New York : Philomel Books, c1996.
"First Scholastic printing, April 1997"--Verso t.p.
Keywords: Literacy -- Fiction; Books and reading -- Fiction; Television -- Fiction